The Effectiveness of Using Comic Strips Toward Students' Reading Comprehension on Narrative Text - Pasha Syiami Ahmad; Sayid Ma’rifatulloh (ELT Worldwide: Journal of English Language Teaching, 2023)
The objective of this study was to examine the potential impact of Comic Strips on the reading comprehension skills of eighth-grade students at Mulia Insani Junior High School in Loa, Bandung-West Java. This study employed a pre-experimental research design, specifically utilizing a pre-test and post-test design. The sample methodology employed in this study was purposive sampling. The research was conducted on the VIII B class at Mulia Insani Junior High School during the academic year 2022/2023. The data was collected by the administration of a reading exam in a multiple-choice format. Next, the obtained data was subjected to analysis using the paired sample t-test. There were a total of four meetings, with two meetings dedicated to therapy and the remaining two meetings allocated for pretest and posttest purposes. The findings of the study indicate a notable impact of using comic strips as a post-treatment intervention, as seen by the observed increase in post-test scores. According to the findings, the average score of the posttest was 87.41, whereas the average score of the pretest was 39.67. Additionally, according to the results of the paired sample t-test, the two-tailed significance value (sig) was found to be 0.000, which is below the conventional threshold of 0.05. The study of the paired sample t-test yielded statistically significant results. Hence, this study provides evidence that the utilization of comic strips has a notable impact on the reading comprehension of students, particularly in relation to narrative material. The research was conducted in the VIII B class at Mulia Insani Islamic Junior High School in Loa, Bandung-West Java.